Description of Clostridium cagae sp. nov., Clostridium rectalis sp. nov. and Hathewaya massiliensis sp. nov., new anaerobic bacteria isolated from human stool samples. (September 2020) - Tall, M.L.; Lo, C.I.; Yimagou, E. Kuete; Ndongo, S.; Pham, T.P.T.; Raoult, D.; Fournier, P.-E.; Fenollar, F.; Levasseur, A.
Abstract: Using culturomics methods, three strains were isolated, identified and characterized following the taxonogenomics concept. Clostridium cagae strain Marseille-P4344 T (=CSURP4344), Clostridium rectalis strain Marseille-P4200 T (=CSURP4200) and Hathewaya massiliensis strain Marseille-P3545 T (=CSURP3545) were isolated from human stool samples. The phylogenetic reconstruction, phenotypic criteria and genomic analyses were carried out and demonstrated that these three bacteria are different from previously known bacterial species with standing in nomenclature and were classified as new members of the Clostridiaceae family.